Business plan : Growth strategy of a propeller's producer - Mejzlík, Tomáš; Lukeš, Martin, 1976-; Andera, Michal, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
This Master’s provides recommendations for an existing producer of carbon-fibre propellers on how to enter a new market with propellers for UAV. The thesis is divided into three key parts. First, theoretical part provides a background on how to design a business model and to write a business plan, introduces trends and success criteria in a drone industry. Second, contains empirical research and maps the UAV propeller market. Those data are a starting point for a third part, a business plan which provides recommendation of possible growth opportunities.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses